The Prins Cascade Cyclization Reaction for the Synthesis of Angularly‐Fused Tetrahydropyran and Piperidine Derivatives. Issue 10 (11th February 2013) - Subba Reddy, B. V.; Kumar, Harish; Borkar, Prashant; Yadav, J. S.; Sridhar, B.
Abstract: 2‐Arylethylbut‐3‐en‐1‐ol is found to undergo smooth Prins cascade reactions with various aldehydes in the presence of Sc(OTf)3 (10 mol‐%) and a stoichiometric amount of TsOH to afford the corresponding trans ‐fused hexahydro‐1 H ‐benzo[ f ]isochromenes in good yields with excellent selectivity. Likewise, N ‐tosyl‐2‐phenethylbut‐3‐en‐1‐amine gives trans ‐fused octahydrobenzo[ f ]isoquinoline derivatives under similar conditions. This is the first example of the synthesis of hexahydro‐1 H ‐benzo[ f ]isochromene and octahydrobenzo‐[ f ]isoquinoline from 2‐arylethylbut‐3‐en‐1‐ol and N ‐tosyl‐2‐phenethylbut‐3‐en‐1‐amine, respectively. Abstract : 2‐Arylethylbut‐3‐en‐1‐ol undergoes a Prins cascade reaction with aldehydes to afford trans ‐fused hexahydro‐1 H ‐benzo[ f ]isochromenes in good yields with excellent selectivity. Likewise, N ‐tosyl‐2‐phenethylbut‐3‐en‐1‐amine gives trans ‐fused octahydrobenzo[ f ]isoquinoline derivatives.